PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA GURU DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIATING PADA YAYASAN PENDIDIKAN MIFTAHUL ULUM ADDINIYAH GANDUL CINERE DEPOK - Laila Fitriyani; Husainah, Nazifah; Haryoto, Cecep (PT Naureen Digital Education, 2023)
This study aims to examine and analyze the influence of the Compensation and Work Environment on Teacher Job Satisfaction with Work Motivation as a Mediating Variable at Miftahul Ulum Educational Foundation Gandul Cinere Depok. The independent variables used are Compensation and Work Environment, while the dependent variable is Job Satisfaction. The data collection method in this study was carried out by distributing questionnaires to 90 respondents at Miftahul Ulum Educational Foundation Gandul Cinere Depok. The research method used is an associative quantitative method using primary data. The results of this study indicate that the Compensation has significant effect on Job Satisfaction with a value t count is greater than t table (4,160 > 1,662) and is significant at (0,000 < 0,05), Work Environment has significant effect on Job Satisfaction with a calculated t value greater than t table (2,761 > 1,662) and is significant at (0,006 < 0,05), Compensation has not significant effect on Job Satisfaction trough Work Motivation with an indirect effect value smaller than the direct influence value (0,117 < 0,225), Work Environment has not significant effect on Job Satisfaction trough Work Motivation with an indirect effect value greater than the direct influence value (0,136 < 0,217), and Work Motivation has significant effect on Job Satisfaction with a value t count is greater than t table (3,127 > 1,662) and is significant at (0,002 < 0,05)